Relaxation Dynamics and Magnetic Anisotropy in a Low‐Symmetry DyIII Complex. Issue 16 (9th March 2016) - Lucaccini, Eva; Briganti, Matteo; Perfetti, Mauro; Vendier, Laure; Costes, Jean‐Pierre; Totti, Federico; Sessoli, Roberta; Sorace, Lorenzo
Abstract: The magnetic behaviour of a Dy(LH)3 complex (LH − is the anion of 2‐hydroxy‐ N ′‐[( E )‐(2‐hydroxy‐3‐methoxyphenyl)methylidene]benzhydrazide) was analysed in depth from both theoretical and experimental points of view. Cantilever torque magnetometry indicated that the complex has Ising‐type anisotropy, and provided two possible directions for the easy axis of anisotropy due to the presence of two magnetically non‐equivalent molecules in the crystal. Ab initio calculations confirmed the strong Ising‐type anisotropy and disentangled the two possible orientations. The computed results obtained by using ab initio calculations were then used to rationalise the composite dynamic behaviour observed for both pure Dy III phase and Y III diluted phase, which showed two different relaxation channels in zero and non‐zero static magnetic fields. In particular, we showed that the relaxation behaviour at the higher temperature range can be correctly reproduced by using a master matrix approach, which suggests that Orbach relaxation is occurring through a second excited doublet. Abstract : Magnetic effects : The combination of cantilever torque magnetometry, advanced ab initio calculations, and ac susceptibility measurements provided a detailed picture of the electronic structure of a new Dy III single‐molecule magnet and its relationship to the rich low‐temperature spin dynamics (see figure).